DOES CORPORATE GOVERNANCE, LIQUIDITY, AND BANK SIZE AFFECT THE EFFICIENCY OF SHARIA BANKS IN INDONESIA? - Ghifar, Adry Daffand; Zakariyya, Muhammad; Tristianto, Erdin Maulana (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: The aim of this research was carried out in order to show whether corporate governance, liquidity, and business size might impact the efficiency of an Islamic bank in Indonesia prior to the merger of three Islamic banks, namely BNI Syariah, BRI Syariah, and Bank Syariah Mandiri, and from 2016 to 2021. Methods: Sharia governance is measured using CEO duality proxies and board size, whereas liquidity is measured using DAR, bank size is calculated using the logarithm of total assets, and bank efficiency is measured using three proxies: managerial efficiency, expenses, and profits. The information was compiled from annual financial reports 2016–2021 of 14 Indonesian Islamic commercial banks. Multiple linear regression and testing of conventional hypotheses are used to process the data in SPSS 25. Results: The results of the hypothesis testing indicate that factors affecting management effectiveness are board size, CEO duality, bank size, and liquidity. Conclusion and suggestion: The observation period of the previous five years can be used in future studies to add measurement indicators to corporate governance factors. In order to acquire more varied results with distinct settings of bank efficiency between conventional banks and Islamic banks, study samples might be used that come from conventional banks in addition to these other choices.